FRI0128 Prism – pictorial representation of illness and self measure: the use of a simple non-verbal tool as a patient-centred outcome measure in early rheumatoid arthritis cohorts. (15th June 2017) - Taylor, PC; Alten, R; Haraoui, B; Amess, B; Macdonald, J; Truchon, M; Pohl, C; Swales, C; Kaneko, Y; Sensky, T
Abstract : Background: Treatment recommendations in early RA advocate a treat to target approach with the ideal goal of remission. But not all patients attain this goal. There is a need for outcome measures that are meaningful to patients and inform management of which alleviation of suffering is a key aim. PRISM 1 is a novel, validated, brief method of measuring suffering consistent with Cassell's seminal conceptualisation 2 . Objectives: To understand the relationships between a patient's perception of the totality of the impact of RA and commonly used clinical assessments of disease activity, depression and illness intrusiveness. Methods: Basic sociodemographic and clinical data were collected from 182 RA patients from 3 international centres, assigned to one of four cohorts (two early RA and two established RA), at baseline, weeks 12 and 24. The two early RA cohorts (diagnosis <2 yr) comprised Group 1 on stable treatment (n=37) and Group 2 requiring csDMARD adjustment (n=34). Using the iPRISM App on a tablet, all patients were asked to complete the basic PRISM task to measure self-illness separation (SIS). The smaller the SIS, the greater the person's perceived suffering. In the PRISM+ task, patients were asked to identify two valued aspects of their life at the moment (X and Y) which bring pleasure, satisfaction, a sense of achievement, or a sense of purpose. The iPRISM App automatically records the distance between the centres of each of these disks and the Self disk to measure patients' perceptions of the intrusiveness of their illness on two personally valued aspects of their lives. For both groups, direction of change in SIS and the PRISM+ measures were compared with direction of change in disease activity measures and patient global disease activity (ptGbl), assessed at wks 12 and 24, using the sign test. Results: PRISM was easy to use and most patients understood the simple instructions. Of 182 patients at baseline, SIS showed significant correlations with ptGbl (rs =-0.48, p<0.0001), pain VAS (rs =-0.45, p<0.0001), PHQ9 (rs =-0.45, p<0.0001) and illness intrusiveness scale (rs =-0.51, p<0.0001). Suffering was inversely correlated with the perceived controllability of the symptoms of RA; for Group 1, rs =0.41, p<0.0001, for Group 2, rs =0.32, p<0.0001. In Group 2, SIS and DAS28-ESR showed small trends to improvement by wk 12 (DAS28-ESR Δ=-0.11, p=0.557; SIS Δ=1.7, p=0.296) with significant improvement by wk 24 (DAS28-ESR Δ=-0.82, p=0.002; SIS Δ=3.85, p=0.029). However, there was no significant improvement in the intrusiveness of the illness on the valued aspects of life over this time period (Actual X, Δ=-0.25, p=0.557; Actual Y, Δ=1.89, p=0.169). Conclusions: PRISM is a novel PRO that quantifies factors salient to each individual with respect to the impact of RA and its treatment while allowing for incorporation of a wide range of such influences. It may have utility as an adjunct to disease activity measures in setting agreed personalised therapeutic targets. References: T Sensky & S Buchi. PLoS ONE 11(5):e0156284, 2016. EJ Cassell. NEJM 306:639–645, 1982. Acknowledgements: This work was financially supported by UCB in the context of an Investigator Initiated Study. Disclosure of Interest: P. Taylor Grant/research support from: Celgene, Galapagos, GlaxoSmithKline, UCB, and Janssen, Consultant for: AbbVie, Bristol Myers Squibb, Eli Lilly and Company, GlaxoSmithKline, Merck, Pfizer, UCB, Biogen, Sandoz and Janssen, R. Alten: None declared, B. Haraoui: None declared, B. Amess: None declared, J. Macdonald: None declared, M. Truchon: None declared, C. Pohl: None declared, C. Swales: None declared, Y. Kaneko Grant/research support from: Eisai, AbbVie, Daiichisankyo, Speakers bureau: Astellas Pharma, Chugai Pharmaceutical Co, Ltd., Bristol–Myers K.K., Eisai Co., Ltd., Kissei Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Taisho Toyama Pharma Co., and UCB, T. Sensky: None declared